Tetrazine‐Responsive Self‐immolative Linkers. (16th December 2016) - Neumann, Kevin; Jain, Sarthak; Gambardella, Alessia; Walker, Sarah E.; Valero, Elsa; Lilienkampf, Annamaria; Bradley, Mark
Abstract: Molecules that undergo activation or modulation following the addition of benign external small‐molecule chemical stimuli have numerous applications. Here, we report the highly efficient "decaging" of a variety of moieties by activation of a "self‐immolative" linker, by application of water‐soluble and stable tetrazine, including the controlled delivery of doxorubicin in a cellular context. Abstract : Freed to kill : Doxorubicin was conjugated to PEG‐ b ‐Dox nanoparticles through a self‐immolative linker, comprised of a vinyl‐ether‐caged phenol that undergoes a 1, 6‐elimination upon DAINV activation with tetrazine, thereby resulting in cargo release and switch‐on of cytotoxicity.